Autonomic hypoactivity in boys with attention-deficit/hyperactivity disorder and the influence of methylphenidate. (January 2014) - Conzelmann, Annette; Gerdes, Antje B. M.; Mucha, Ronald F.; Weyers, Peter; Lesch, Klaus-Peter; Bähne, Christina G.; Fallgatter, Andreas J.; Renner, Tobias J.; Warnke, Andreas; Romanos, Marcel; Pauli, Paul
Abstract Objectives. This study investigates an overall autonomic hypoactivity reflecting hypoarousal as important aetiological factor in ADHD at baseline during rest and in response towards stimuli. In addition, effects of methylphenidate (MPH) are examined. We further assessed whether this hypoarousal is a stable characteristic or ameliorated by arousing emotional stimuli. Methods. Boys with ADHD were examined with (n = 35) or without MPH (n = 45) and compared with healthy boys (n = 22) regarding skin conductance level (SCL) during rest and skin conductance responses (SCRs) as well as valence and arousal ratings in response to positive, neutral, and negative pictures. Results. ADHD children without MPH were characterized by reduced baseline SCL and overall reduced SCRs. ADHD children with MPH never differed from control children. All groups displayed normal valence and arousal ratings of the stimuli and enhanced SCRs to emotional in comparison to neutral pictures. Conclusions. This is the first study to unravel (1) a general autonomic hypoactivity in ADHD children at baseline and in response to low arousing neutral and highly arousing emotional stimuli, and (2) hints that MPH normalizes this hypoactivity. Results contribute to the understanding of ADHD aetiology and MPH functionality, and are consistent with the cognitive-energetic model of ADHD.